Upaya Guru Akidah Akhlak Dalam Membangun Karakter Kesantunan Peserta Didik Di Madrasah Aliyah Negeri 2 Garut - Raito, Raito; Putri, Angelina Setiawati (STAI Al-Musaddadiyah Garut, 2024)
This research is motivated by the problem of the character of politeness of students as the next generation of the nation caused by several factors such as the influence of globalization, the use of social media, and the influence of the surrounding environment which causes the fading of the character of politeness in students, both at the elementary, junior high, and high school levels. Similarly, Madrasah Aliyah Negeri (MAN) 2 Garut which is the target of this research, that the problem of the character of students, especially those related to the character of politeness, still shows many gaps that occur in the lives of students in the environment of MAN 2 Garut. It is realized that politeness character education for students is very important to be carried out through planting, forming, habituation, and exemplary practiced by teachers, students, and all elements of educational actors, especially at MAN 2 Garut. Given the character of politeness for students is a fundamental thing that is always attached to him in every action and behavior. The objectives of this research are; 1) Describing the Character Development of Politeness of Learners; 2) Describing the Character of Politeness of Students at MAN 2 Garut; 3) Describing the Efforts of Akidah Akhlak Teachers in Building the Character of Politeness of Students at MAN 2 Garut. This type of research is field research, the method used is descriptive qualitative method with a phenomenological approach that describes the phenomena and events that actually occur at MAN 2 Garut. The data collection techniques used are structured observation, structured interviews, and documentation. The data analysis technique is by means of data collection, data reduction, data presentation, verification and conclusion. The results of this study indicate that at MAN 2 Garut there are several problems related to the character of politeness of students, namely: Abusive words to friends, not paying attention when the teacher explains, arguing with friends about differences in opinion, not greeting when meeting the teacher, and dressing in a less polite manner. Efforts made by several moral akidah teachers at MAN 2 Garut include: applying sanctions, applying polite characters, increasing religious understanding, increasing cooperation between the school and student guardians, negligence, having good character, and holding religious extracurricular activities. Keywords: Efforts Akidah Akhlak Teacher, Character Politeness